2022
DOI: 10.1039/d2cy00935h
|View full text |Cite
|
Sign up to set email alerts
|

Quantum yield enhancement in the photocatalytic HCOOH decomposition to H2 under periodic illumination

Abstract: Despite numerous studies on controlled periodic illumination to improve the quantum yield of photocatalytic reactions, debates still exist on the nature of the enhancement effect. Here, we report the promotion...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 74 publications
0
10
0
Order By: Relevance
“…The intense peak at 27.7°corresponds to plane (002), portrays the graphitic nature of the materials, and belongs to the standard interlayer stacking structure of g-C 3 N 4 (JCPDS87-1526). 37 Another weak diffraction peak at 13.1°signies the (100) plane, conrming the interplanar structural packing in g-C 3 N 4 . 38 Upon ultrasonication, exfoliation of the layered Scheme 2 Schematic presentation for the synthesis of g-C 3 N 4 and X% Pd@E-g-C 3 N 4 .…”
Section: Resultsmentioning
confidence: 99%
“…The intense peak at 27.7°corresponds to plane (002), portrays the graphitic nature of the materials, and belongs to the standard interlayer stacking structure of g-C 3 N 4 (JCPDS87-1526). 37 Another weak diffraction peak at 13.1°signies the (100) plane, conrming the interplanar structural packing in g-C 3 N 4 . 38 Upon ultrasonication, exfoliation of the layered Scheme 2 Schematic presentation for the synthesis of g-C 3 N 4 and X% Pd@E-g-C 3 N 4 .…”
Section: Resultsmentioning
confidence: 99%
“…The photocurrent of the KNbO 3 catalyst showed that the introduction of non-metallic element N can improve the separation efficiency of photogenerated electrons and holes. 32 Moreover, Fig. 4b shows the electrochemical impedance spectra (EIS).…”
Section: Resultsmentioning
confidence: 99%
“…The apparent quantum yield (AQY) was calculated following a reported method. 40 The details of photocatalytic reactions, photocatalytic reactor set-up, quantification of conversion, selectivity (Fig. S1), and AQY are provided in the ESI †.…”
Section: Methodsmentioning
confidence: 99%